Macrocyclic receptors for environmental and biosensing applications. (2022) - (Chemistry professor), Kumar, Satish; Sahoo, Priya Ranjan; Macwan, Violet Rajeshwari; Kaur, Jaspreet; Mukesh; Sahney, Rachana
No abstract available